Workshop Pengembangan Video Pembelajaran Bagi Guru MI Muhammadiyah Program Khusus Tegalampel, Klaten - Muhamad Taufik Hidayat; Ummi Tadzkiroh; Najla Febi Nadhila; Albi Arangga (CV. Ulil Albab Corp, 2023)
The purpose of this service activity are (1) Providing knowledge to participants regarding the creation of teaching materials using learning media based on information technology and the internet. (2) Provide skills in making learning videos based on information technology and the internet through the Zoom Meeting application. The method used in this training is a combination of lectures, questions and answers, discussions, and hands-on practice. Given the pandemic period, the implementation is carried out according to health protocols so that participants maintain distance. The training material is divided into two, namely how to make interesting learning materials and how to record video learning materials through Zoom Meetings. Thisservice activity can support the learning process, it can also increase the credibility of the school. The implementation of the training was highly appreciated by the school. They hope to be able to practice what has been obtained in this training and still want to be given assistance